Student’s thinking processes on bloom’s taxonomy: exploring direct instruction learning model - A Widayanto; H Pratiwi; M Mardiyana (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This research aimed to describe the levels of thinking students in mathematical problem-solving based on Bloom's taxonomy as seen from Direct Instruction learning model. The cognitive domain contains intellectual-centered behavior, such as knowledge, and thinking skills. Direct Instruction is an instructional model that focuses on the interaction between teachers and students. The type of this research is descriptive research with a qualitative approach. The research subjects were taken by one student in Direct Instruction learning model which then given the mathematical problem-solving test and the result was triangulated by interview. From this research, it is found that Direct Instruction student can achieve analyzing thinking level.